2010
DOI: 10.1039/b9ay00158a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of additives in a commercial electroplatingnickel bath by spectrophotometry and multivariate analysis

Abstract: An electroplating nickel bath is usually composed of a number of organic additives to improve the plating process as well as to preserve its durability. Supreme Plus Brightener (SPB) and A-5(2X), used in a commercial electroplating nickel bath show highly overlapped UV-Vis spectra. These two additives are the only ones that present absorbance in the UV-Vis wavelength range. Therefore, a mixture of them can be resolved using multivariate calibration methods of UV-Vis measurements. In this work, Partial Least Sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The noise contained in the spectral information is one of key factors significantly influencing the prediction of NIRS analysis. Chemometrics, which involves spectra preprocessing and multivariate calibration methods, is an efficient tool to eliminate or reduce spectra noise and improve NIRS prediction (Azzouz et al, 2003; Vidal et al, 2010). In most previous studies, the most common preprocessing methods, such as standard normal variate, multiplicative scatter correction, derivative, and smoothing, were usually used.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…The noise contained in the spectral information is one of key factors significantly influencing the prediction of NIRS analysis. Chemometrics, which involves spectra preprocessing and multivariate calibration methods, is an efficient tool to eliminate or reduce spectra noise and improve NIRS prediction (Azzouz et al, 2003; Vidal et al, 2010). In most previous studies, the most common preprocessing methods, such as standard normal variate, multiplicative scatter correction, derivative, and smoothing, were usually used.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…UV-Visible spectroscopy, together with classical least squares (CLS) or inverse least squares (ILS) calibration, was used for determination of additives in Ni-Zn baths [3]. More recently, additives in Ni baths have also been determined using UV-Visible spectroscopy with partial least squares (PLS) calibration [4]. The use of NMR spectroscopy to follow the additive behavior in an electrolytic Zn bath [5] and the potential of this technique for the quantitation of additives in an acidic Zn bath has also been shown [6].…”
Section: Introductionmentioning
confidence: 99%
“…Three kind of additives were included in the model in order to control the local surface growth rate. Partial least square (PLS) regression and classical least square (CLS) were used by Vidal et al [12] to quantify both additives during the whole duration of electroplating nickel bath. It was found that PLS regression provided the best results.…”
Section: Introductionmentioning
confidence: 99%